Dissociative symptomatology in cancer patients - Civilotti, Cristina; Castelli, Lorys; Binaschi, Luca; Cussino, Martina; Tesio, Valentina; Di Fini, Giulia; Veglia, Fabio; Torta, Riccardo (Frontiers in Psychology, 2015)
INTRODUCTION: The utilization of the post-traumatic stress disorder (PTSD) diagnostic spectrum is currently being debated to categorize psychological adjustment in cancer patients. The aims of this study were to: 1) evaluate the presence of cancer-related traumatic dissociative symptomatology in a sample of cancer patients; 2) examine the correlation of cancer-related dissociation and sociodemographic and medical variables, anxiety, depression and post-traumatic stress symptomatology; 3) investigate the predictors of cancer-related dissociation. METHODS: Ninety-two mixed cancer patients (mean age: 58,94, ds=10,13) recruited from two hospitals in northern Italy were administered a questionnaire on sociodemographic and medical characteristics, the Karnofsky Scale to measure the level of patient activity and medical care requirements, the Hospital Anxiety and Depression Scale (HADS) to evaluate the presence of anxiety and depression, the Impact of Event Scale Revised (IES-R) to assess the severity of intrusion, avoidance and hypervigilance, and the Peritraumatic Dissociative Experiences Questionnaire (PDEQ) to quantify the traumatic dissociative symptomatology. RESULTS: 31.5% of participants report a PDEQ score above the cutoff. The results indicated that dissociative symptomatology was positively correlated with HADS scores (HADS-Anxiety: r=.476, p<.001; HADS-Depression: r=.364, p<.001) and with IES-R scores (IES-R-Intrusion: r=.698, p<.001; IES-R-Avoidance: r=.619, p<.001; IES-R- Hypervigilance: r=.681, p<.001). A stepwise regression analysis was performed in order to find the predictors of cancer-related traumatic dissociative symptomatology. The results converged on a three predictor model revealing that IES-R-Intrusion, IES-R-Avoidance and IES-R-Hyperarousal accounted for 53.9% of the explained variance. CONCLUSIONS: These findings allow us to hypothesize a specific psychological reaction which may be ascribed to the traumatic spectrum.